Salinomycin exhibits anti-angiogenic activity against human glioma in vitro and in vivo by suppressing the VEGF-VEGFR2-AKT/FAK signaling axis - Bi, Yan-Ling (Int J Mol Med, 2017)
Tumor angiogenesis plays a crucial role in tumor growth, progression and metastasis, and suppression of tumor angiogenesis has been considered as a promising anticancer strategy. Salinomycin (SAL), an antibiotic, displays novel anticancer potential against several human cancer cells in vitro and in vivo. However, little information concerning its anti-angiogenic properties is available. Therefore, the anti-angiogenic effect of SAL and the underlying mechanism in human glioma were evaluated in the present study. The results indicated that SAL treatment significantly inhibited human umbilical vein endothelial cell (HUVEC) proliferation, migration, invasion and capillary-like tube formation. Further investigation on intracellular mechanisms showed that SAL markedly suppressed FAK and AKT phosphorylation, and downregulated vascular endothelial growth factor (VEGF) expression in HUVECs. Pretreatment of cells with a PI3K inhibitor (LY294002) and FAK inhibitor (PF562271) markedly enhanced SAL-induced inhibition of HUVEC proliferation and migration, respectively. Moreover, U251 human glioma xenograft growth was also effectively blocked by SAL treatment in vivo via inhibition of angiogenesis involving FAK and AKT depho sphorylation. Taken together, our findings validated that SAL inhibits angiogenesis and human glioma growth through suppression of the VEGF-VEGFR2-AKT/FAK signaling axis, indicating the potential application of SAL for the treatment of human glioma.